Screening for Tobacco and Nicotine Use in Pregnancy. Issue 3 (May 2017) - Wisner, Kirsten
Abstract : Nearly 10 percent of women in the United States report smoking at one time during their pregnancy. Screening for tobacco and nicotine use during pregnancy is important to identify women who need help with smoking cessation. Various types of tobacco and nicotine products are discussed to familiarize nurses with new products that women should be asked about during pregnancy in addition to cigarettes. Smoking cessation toolkits and resources for clinicians are presented.